Tax Avoidance Culture and Employees' Behavior Affect Sustainable Business Performance: The Moderating Role of Corporate Social Responsibility - Li, Yan; Al-Sulaiti, Khalid; Dongling, Wang; Abbas, Jaffar; Al-Sulaiti, Ibrahim (Frontiers in Environmental Science, 2022)
Employees' behavior and corporate social responsibility (CSR) can affect firms' profitability and increase the corporate economic burden. This current research endeavors to explore how business firms navigate employees' technology-driven behavior and CSR sustainable practices for tax avoidance to affect firms' performance. This study examines how CSR sustainable practices moderate the relationship between employees' behavior and tax avoidance to achieve sustainable business performance. The study incorporated the Maximum Likelihood Estimator (MLE) for the purpose of data analysis using the structural equation modeling (SEM) technique that is suitable for this sample size. The study's target population is employees of small and medium enterprises located in Pakistan. The study has drawn a sample of employees and applied a convenience sampling technique. The findings show that tax avoidance, employee behavior, and corporate social responsibility positively affect business firms' performance. The results further indicate that sustainable CSR practices significantly moderate tax avoidance's effect on business firms' performance. However, there is no condition to identify the relationship between employee behavior and firm performance. In theory, this research contributes to the corporate strategy literature by answering how corporate social responsibility sustainable practices mediate the relationship between tax avoidance, employees' behavior, and sustainable business performance. It shows that socially responsible organizations will engage less in tax avoidance behaviors. The results exhibit that the study provides a systematic, holistic framework to attain sustainable firms' performance. The findings' generalizability offers future direction with helpful insights for business managers and policymakers.